Wernicke Encephalopathy in a Child with Acute Lymphoblastic Leukemia with Atypical Neuroimaging Findings - Cornelius, Leema; Paulraj, Asir; Elango, Neeraj (Indian Journal of Medical and Paediatric Oncology, 2020)
Wernicke encephalopathy (WE) is characterized by a clinical triad of ataxia, ophthalmoplegia, and altered mental state. It is said to be a rare entity in infants and children. We describe the case of a 2-year-old child with acute leukemia on chemotherapy who presented with acute encephalopathy. Blood parameters and cerebrospinal fluid analysis were normal, and magnetic resonance imaging of the brain revealed isolated cranial nerve nuclei involvement. There was remarkable improvement in sensorium following thiamine therapy. A high index of suspicion is necessary to diagnose WE in high-risk patients such as leukemia.
Keywords: Acute encephalopathy; acute lymphoblastic leukemia; Wernicke encephalopathy